2015
DOI: 10.1097/spv.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Decision Aid on Decision Making for the Treatment of Pelvic Organ Prolapse

Abstract: In this relatively small sample, the addition of a DA to SC for women with POP does not significantly decrease the level of decisional conflict in making treatment-related decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 8 publications
0
16
1
Order By: Relevance
“…It is noted that 2 randomized studies focused on decision conflict showed no difference, 18, 23 and the remainder indicated that conflict decreased with use of SDM. However, all non-randomized studies that focused on decision conflict as a primary outcome found that decision conflict decreased with the introduction of SDM.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is noted that 2 randomized studies focused on decision conflict showed no difference, 18, 23 and the remainder indicated that conflict decreased with use of SDM. However, all non-randomized studies that focused on decision conflict as a primary outcome found that decision conflict decreased with the introduction of SDM.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies 18, 20, 21, 23, 34, 39, 47, 50, 52, 54 were low risk of bias for random sequence allocation with one 51 having unknown risk of bias. For allocation concealment bias, 3 studies had unknown risk of bias 18, 23, 39 , with the remaining 8 having low risk of bias 20, 21, 34, 47, 50–54 . There was high risk of bias for blinding of participants and personnel in 8 studies which were not double-blinded 18, 20, 21, 23, 39, 47, 51, 53, 54 , with only 3 studies being blinded for either 2, 50, 52 .…”
mentioning
confidence: 99%
See 3 more Smart Citations